Impacts of 60Co-γ irradiation on physicochemical characteristics and antioxidant activity of Tibetan medicine Pazhu powder (PP) - Yue Yang; Le Zhong; Rang yan po Luo; Zhong si ji Yang; Weishan Qiu; Juhong An; Rui Gu; Shihong Zhong (Nuclear Engineering and Technology, 2025)
In order to explore the effect of 60Co-γ irradiation on the quality of Tibetan medicine preparations, this study selected Pazhu powder (PP) which has complex and diverse components for research. PP was irradiated at doses of 3, 6, 10, 15, 20, 50, and 100 kGy of 60Co-γ, Then the effects on color, odor, structural characterization, chemical composition and antioxidant activity were investigated. Results showed that after irradiation, the color, the content of aldehydes and ketones in volatile components were not changed. While the structure and the HPLC fingerprints changed slightly. However, the contents of terpenes, alkanes, amides and alcohols in the volatile components, and all the non-volatile components showed a dose-related decline in irradiated samples. Furthermore, the antioxidant activity increased after irradiation. These findings suggest that 60Co-γ irradiation has a great influence on the chemical composition of PP. It's necessary to cautiously set reasonable irradiation dose for Tibetan medicine preparations.